The horse law of 1888: between the research of the “order” and the construction of an enemy (2012)
In this article it is analyzed the unavoidable relationship that exists between the expedition of laws, the motives to expedite them and the state politics, and how this activity is made with the intention to instrumentalize the criminal law for determina